Pengaruh Kecerdasan Emosional dan Stres Kerja Terhadap Kinerja Karyawan Bagian Produksi Kaos Kaki pada Pt Kahatex Cijerah Kota Cimahi Jawa Barat - Dahlan Ramdhani; Pepri Sulistiani Muningsih (Pusat Riset dan Inovasi Nasional, 2024)
His research aims to determine emotional intelligence and work stress on employee performance, as well as to determine the magnitude of the influence of emotional intelligence and work stress both partially and simultaneously on the performance of employees in the sock production section of PT Kahatex Cijerah, Cimahi City. The type of research used in this research is descriptive and associative methods. The number of samples used in this study were 100 respondents who were taken from all employees of the production section, the socks department. To see the relationship between 2 variables, the analysis used is path analysis. This study resulted that the effect of emotional intelligence on performance partially was 35.4%. The effect of work stress on performance partially is 39.4%, so that emotional intelligence and work stress together (simultaneously) are 74.8% while the rest is influenced by other variables not examined.